Downstream Effects of Haemoglobinase Inhibition in Plasmodium falciparum-Infected Erythrocytes - BELL, ANGUS (My University, 2010)
Blood-stage malarial parasites (Plasmodium falciparum) digest large quantities of host haemoglobin during their asexual development in erythrocytes. The haemoglobin digestion pathway, involving a succession of cleavages by various peptidases, appears to be essential for parasite development and has received much attention as an antimalarial drug target. A variety of peptidase inhibitors that have potent antimalarial activity are believed to inhibit and/or kill parasites by blocking haemoglobin digestion. It has not however been established how such a blockage might lead to parasite death. The answer to this question should lie in identifying the affected physiological function, but the purpose of excess haemoglobin digestion by P. falciparum has for many years been the subject of debate. The process was traditionally believed to be nutritional until Lew VL et al. [Blood 2003;101:4189-94] suggested that it is linked to volume control of the infected erythrocyte and is necessary to prevent premature osmotic lysis of the host cell. Their model predicts that sufficient inhibition of haemoglobin degradation should result in premature haemolysis. In this study we examined the downstream effects of reduced haemoglobin digestion on osmoprotection and nutrition. We found that inhibitors of haemoglobinases (plasmepsins, falcipains and aminopeptidases) did not cause premature haemolysis. The inhibitors did however block parasite development and this effect corresponded to a strong inhibition of protein synthesis. The effect on protein synthesis (i) occurred at inhibitor concentrations and times of exposure that were relevant to parasite growth inhibition, (ii) was observed with different chemical classes of inhibitor, and (iii) was synergistic when a plasmepsin and a falcipain inhibitor were combined, reflecting the well-established antimalarial synergism of the combination. Taken together, the results suggest that the likely primary downstream effect of inhibition of hemoglobin degradation is amino acid depletion, leading to blockade of protein synthesis, and that the parasite probably degrades globin for nutritional purposes.
PUBLISHED
Keywords: malaria; Plasmodium falciparum; Immunology, Inflammation & Infection; International Development